Exploring the Mediating Effect of Brand Image on the Relationship between Social Media Marketing, Green Marketing, and Purchase Decisions - Tamam Arya; Fredianaika Istanti (Jurnal Ragam Pengabdian, 2026)
Consumer behavior in making decision is becoming increasingly diserve, extending in order to fulfill the functional needs and emotional needs as well. In the process of fulfilling these needs, consumers are influenced by factors that drive their decision making. Social media marketing and green marketing are examples of factors that influence consumers in making purchasing decision. The intention of this study is examine the effect of social media marketing and green marketing on purchasing decision, with brand image as a mediating variable among consumers of The Body Shop Indonesia in Semarang City. This study was concern on the growth of intensity of social media usage as primary source of information and focused on consumers awareness of environmental sustainability issue in purchasing selfcare product. This research using quantitative approach with explanatory research design. The sampling technique that implemented in this study was purposive sampling, targeting consumers who have previously purchased product from The Body Shop Indonesia. Data on this study was collected through a structured questionnaire and analyzed using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method to assess validity, reliability, and the structural relationship between variables. The expected result from this research is showing the positive direct effect of social media marketing and green marketing on purchasing decision and positive indirect effect through brand image as mediator. The invention from this study is expected can provide theoretical contributions to the advancement of sustainable marketing and consumer behavior literature, also offering practical implications for companies in formulating effective and sustainability-oriented marketing strategies.